Financial management in Muslim families: Amina Wadud’s feminist perspective on gender equality - Fadhlullah, Fathan (Jurnal Anifa: Studi Gender dan Anak, 2025)
This study explores financial management within Muslim families from the perspective of Islamic feminism, focusing on the thought of Amina Wadud, who emphasizes the principle of gender equality. In many traditional contexts, financial decision-making is predominantly controlled by husbands, while wives are largely confined to managing domestic expenditures. Such practices are often reinforced by patriarchal cultural norms and conservative interpretations of religious texts. Employing a normative qualitative approach with a library research method, this study analyzes Qur’anic exegesis, Islamic feminist scholarship, and academic literature on gender equality to identify values of justice and collaboration in family financial arrangements. The analysis demonstrates that Amina Wadud’s perspective supports a participatory model of financial management, in which both spouses are equally involved in planning, allocating, and deciding on household finances. This model reflects a more equitable framework and aligns with the ethical principles of justice within Islamic teachings. Women’s active participation in financial decision-making contributes to improved family well-being and greater household economic resilience. However, the persistence of cultural resistance and rigid religious interpretations remains a significant challenge. Therefore, this study underscores the importance of gender equality education, women’s empowerment, and policy reform as strategic efforts to promote justice and balance in the financial structures of Muslim families.